Cascading lake drainage on the Greenland Ice Sheet triggered by tensile shock and fracture - Christoffersen, Poul; Bougamont, Marion; Hubbard, Alun; Doyle, Samuel H.; Grigsby, Shane; Pettersson, Rickard (Nature Communications, 2018)
Source at https://doi.org/10.1038/s41467-018-03420-8 . Supraglacial lakes on the Greenland Ice Sheet are expanding inland, but the impact on ice flow is equivocal because interior surface conditions may preclude the transfer of surface water to the bed. Here we use a well-constrained 3D model to demonstrate that supraglacial lakes in Greenland drain when tensile-stress perturbations propagate fractures in areas where fractures are normally absent or closed. These melt-induced perturbations escalate when lakes as far as 80 km apart form expansive networks and drain in rapid succession. The result is a tensile shock that establishes new surface-to-bed hydraulic pathways in areas where crevasses transiently open. We show evidence for open crevasses 135 km inland from the ice margin, which much farther inland is than previously considered possible. We hypothesise that inland expansion of lakes will deliver water and heat to isolated regions of the ice sheet’s interior where the impact on ice flow is potentially large